2021
DOI: 10.1016/j.dcn.2021.100993
|View full text |Cite
|
Sign up to set email alerts
|

Social neural sensitivity as a susceptibility marker to family context in predicting adolescent externalizing behavior

Abstract: Highlights We examined brain function during anticipation of social reward and punishment. Neural sensitivity reflected increased susceptibility to negative family contexts. For youth high in sensitivity, family conflict predicted externalizing behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 60 publications
5
16
0
Order By: Relevance
“…Overall, these results are consistent with literature linking greater neural reactivity in the subcortical reward network to behavior changes in different social environments 13,14,15 . However, the study did have several limitations to consider.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, these results are consistent with literature linking greater neural reactivity in the subcortical reward network to behavior changes in different social environments 13,14,15 . However, the study did have several limitations to consider.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, those with lower reward response may be resilient in the face of negative influence but may also be less likely to experience benefits when in positive environments. Similar effects may also be found in a single direction; for example, greater sensitivity in reward regions of the brain in response to social reward or punishment modulates adolescent risk taking 13 and externalizing behavior 14 in negative environments, while other biological markers have been shown to modulate positive environments 15 . However, the link between reward susceptibility and social well-being within socially rich or impoverished environments has not yet been studied.…”
Section: Research Highlightsmentioning
confidence: 84%
“…For example, iron rich diets and supplements may decrease lead concentration in blood (Kordas, 2017). Similarly, selenium supplements may help to mitigate health effects related to mercury toxicity (Spiller et al., 2018). In research on psychosocial moderators of the link between pollutant exposure and adverse health outcomes, the associations between air pollution and stress biology in adolescents are stronger in youth who report experiencing more severe mental health difficulties (Miller et al., 2020; Miller et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of newborn infants, Overfeld et al. (2020) found that postnatal enrichment was positively associated with early cognitive development only in infants with larger hippocampal volume. Across these studies, individuals with smaller hippocampal volume appear to be less sensitive to both the costs and the benefits associated with environmental support and adversity (Overfeld et al., 2020; Schriber et al., 2017; Whittle et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation